Metaphor As A Stylistic Device In Text Linguistics - Xolbayev Farrux Uskanovich; Mahmudova Komila Sobirjanovna (Research Parks Publishers, 2023)
the research aims to identify the conceptual metaphor underlying metaphorical linguistic expressions in key texts by five of the greatest English language stylists. It then compares these expressions to their Bulgarian translations to see if the metaphor is lost or changed in any way. Conclusions about translated literature are drawn, outlining instances when the kind and quantity of metaphors are similar to those in original material.